Risk of chronic kidney disease in people living with HIV by tenofovir disoproxil fumarate (TDF) use and baseline D:A:D chronic kidney disease risk score. Issue 5 (28th November 2020) - Hsu, R; Brunet, L; Fusco, J; Beyer, A; Prajapati, G; Wyatt, C; Wohlfeiler, M; Fusco, G
Abstract : Objectives: To assess the risk of chronic kidney disease (CKD) associated with tenofovir disoproxil fumarate (TDF) use by baseline D:A:D CKD risk score. Methods: Adult antiretroviral therapy (ART)‐naïve people living with HIV (PLWH) initiating treatment, with estimated glomerular filtration rate (eGFR) ≥ 60 mL/min/1.73 m 2, were identified in the OPERA cohort. CKD was defined as two or more consecutive eGFR < 60 mL/min/1.73 m 2, > 90 days apart. Associations between TDF use, baseline D:A:D CKD risk and incident CKD were assessed with incidence rates (IRs; Poisson regression) and adjusted pooled logistic regression. The impact of pharmacoenhancers on the observed association between TDF and CKD was also evaluated. Results: Of 9802 PLWH included, 6222 initiated TDF and 3580 did not (76% and 79% low D:A:D CKD risk, respectively). Overall, 125 CKD events occurred over 24 382 person‐years of follow‐up. Within strata of D:A:D CKD risk score, IRs were similar across TDF exposure, with high baseline CKD risk associated with highest incidence. Compared with the low‐risk group without TDF, there was no statistical difference in odds of incident CKD in the low‐risk group with TDF (adjusted odds ratio = 0.55, 95% confidence interval: 0.19–1.54). Odds of incident CKD did not differ statistically significantly by pharmacoenhancer exposure, with or without TDF. Conclusions: In this large cohort of ART‐naïve PLWH, incident CKD following ART initiation was infrequent and strongly associated with baseline CKD risk. TDF‐containing regimens did not increase the odds of CKD in those with a low baseline D:A:D CKD risk, the largest group of ART‐naïve PLWH, and may remain a viable treatment option in appropriate settings.